The Motive of Thunderstruck Tree in Connection to Wedding Customs - Sinkevičius, Rokas (Tautosakos darbai, 2018)
Latvian folksongs of three types (LD 33802, 34043, 34047) and a Lithuanian song Aušrinė (‘the Morning Star’) published by Liudvikas Rėza (Ludwig Rhesa, RD I 62) depict a tree struck by the Thunderer (Latvian Perkons). The kind of the tree may vary: usually, it is an oak, but sometimes it may be an apple-tree. Researchers of Latvian mythology and folklore call it Saules koks (‘the tree of the Sun’). In different variants, the striking of the tree tends to be part of the plot of the heavenly wedding. Sometimes Perkons allegedly strikes the tree in order to express his objections regarding the Sun’s decision to marry off her daughter to an “unsuitable” groom. Scholars interpret this image of the thunderstruck tree in different ways. Wilhelm Mannhardt thought the image to have stemmed from a natural phenomenon – the rays of the setting Sun. Vyacheslav Ivanov and Vladimir Toporov attributed this motive to the symbol of the World Tree and the Indo-European “basic myth” that they had reconstructed. According to Pranė Dundulienė, the thunderstruck oak is a symbolic representation of the bridegroom. Having amassed considerable ethnographic and folklore data, the author of this article questions the earlier explanation presented by Leopold von Schröder and Haralds Biezais. According to them, the motive of Perkons striking the oak may stem from the traditional Latvian wedding custom: the bride’s coachman makes a sign of the cross on the gate or the door with his sword upon arrival, imitating the cutting. Our analysis employs the comparative method. The appreciation of this motive requires considering the connections between the Thunderer and the oaks that exist in numerous ancient Indo-European religions (including Greek, Roman, Celtic, and Baltic). The lightning strike to the oak, possibly, only added some extra meaning to this connection (the thunderstruck wood was used for magic purposes), which emphasized power and strength attributed both to the thunder and the oak. The plausibility of relating the powerful celestial oak to the sacred tree of the homestead would require further discussions. Some variants of the mythological folksongs suggest that the oak hit by Perkons must have been growing by the gate. However, in folksongs and customs, this particular location emerges as liminal and unsafe in relation to home. Although Biezais used the Latvian example, similar customs of imitated cutting of the gate, door, or beam are also widespread in the Eastern Slavic lands. This enables us to understand better their nature, variations, and possible origins. Currently, we can use more ample Latvian and Lithuanian data. In wedding customs, actions similar to cutting or striking mostly indicate the active or masculine principle, including clashing between the bride’s and the groom’s parties, and invading of the foreign territory; but generally are characteristic of both sides. The fierce and militant character of Perkons is especially evident in this liminal sphere; there, as wedding customs and songs clearly indicate, also the hardest clash between the opposing parties takes place at some stage of the wedding. Although this clash is most prominent at the beginning of the wedding ceremony (during matchmaking, and particularly when representatives of the groom arrive to take the bride to her new home), certain “active response” is also evident in the way that the bride’s party behaves at the gate or door of the groom’s house. This may also include new elements, such as threatening to break the table with a specific musical instrument. Taunting of the wedding parties while using similar images and formulas to those used by folksongs describing animals enable us to see more clearly some peculiarities of the Thunderer’s image apparent in the songs describing the heavenly wedding (his attribution to the bride’s party and unexpectedly destructive character). The selected folklore and customs serve to considerably widen and deepen the possibilities of discussing the hypothesis raised by von Schröder and Biezais. However, this does not solve the main issues inherent in the substantiation of this hypothesis – e. g., it contradicts the authentic storylines of the songs describing the heavenly wedding; objects that are cut differ as well, while the consequences of the action – the destruction of the oak – do not ground its possible ritual purpose. The use of the sign of the cross is also ambivalent in customs, since it can serve both as means of protection against the adversary of the Thunderer – the devil, and against the thunder itself. However, the collected comparative materials provide a better idea regarding the meaning of this mythic thunder strike in the wedding contexts, elucidating certain regularities and inconsistencies.